Qualitative GIS a mixed methods approach - Cope, Meghan; Elwood, Sarah (Los Angeles, [Calif.] London SAGE, 2009)
Geographic information systems (GIS) are an essential tool for analyzing and representing quantitative spatial data. This title explains the recent integration of qualitative research with GIS.
Includes bibliographical references and index.
Keywords: Geographic information systems; Qualitative research; Electronic books